On sand-bearing myxillid sponges, with a description of Psammochela tutiae sp. nov. (Poecilosclerida, Myxillina) from the northern Moluccas, Indonesia - de Voogd, Nicole J. (Zootaxa, 2012)
Sand-bearing sponges belonging to the suborder Myxillina are mainly observed in South Australia. Recent biodiversitysurveys in Indonesia yielded several of these sand-bearing sponges belonging to three different genera, Chondropsis, Des-mapsamma and Psammochela. These sponges are distributed across three different families and the ecological and evo-lutionary implications for the incorporation of sand and detritus in the skeleton remain unresolved so far. In the presentpaper Psammochela tutiae sp.nov. (Poecilosclerida: Myxillina: Myxillidae) is described from the northern Moluccas, In-donesia. The new species is compared with all other (five) Psammochela species occurring in the Indo-West Pacific. Thenew species differs from the other species by overall morphology, absence of polydentate chelae and presence of thinstrongylote megascleres. The current position of Psammochela within the Myxillidae and its relation to other arenaceous Myxillina are discussed here, and an identification key to all known species of Psammochela is given.